Imported Plasmodium falciparum malaria in Istanbul, Turkey: risk factors for severe course and mortality. (October 2013) - Arslan, Ferhat; Mert, Ali; Batirel, Ayse; Inan, Asuman; Balkan, Ilker Inanc; Nazlican, Ozcan; Uzun, Cengiz; Vahaboglu, Haluk
We describe the epidemiological, clinical features and risk factors for the morbidity and mortality of imported Plasmodium falciparum malaria cases during the last 10 years in Istanbul, Turkey. The epidemiological, clinical and laboratory data of cases in six tertiary care hospitals in Istanbul between 2002 and 2012 were analysed. Seventy patients (65 males, five females; median age 37; range: 14–84) were included. Sixty-five (93%) patients had travelled to African countries and the remaining five to other malarious countries. Seventeen (24%) had a history of previous malarial episodes; eight (13%) developed recrudescence during the first month; 22 (31%), 17 (24%), 20 (29%) and three (4%) cases had cerebral malaria, cholestatic icterus, malarial hepatitis and respiratory distress syndrome on admission, respectively. Six of 12 patients with severe falciparum malaria died. Clinically, the presence of alteration in mental status, icterus, hypoglycaemia, disseminated intravascular coagulation and malarial hepatitis were statistically significant for the development of severe malaria and mortality. Recrudescence should not be forgotten, especially in uncomplicated cases.